Effect of Garlic and Alcoholic Extract on the Mitrogenic Soralene Antifungal in Mushrooms Aspergillus amstelodami - Rafea Al-Taee; Rafeah Jarjees (College of Education for Pure Sciences, 2007)
This study includes testing the effect of four subinhibitory concentrations of garlic extracts (aqueous and alcoholic) on the mutagenicity of 8-methoxypsoralen (8-MOP) in the presence of long wave ultraviolet (UV A) in conidia of the fungus Aspergillus amstelodami .The concentrations of aqueous extract were used in this study are (2.5 , 5 , 7.5 and 10 mg I ml media ) and the concentrations of alcoholic extracts are ( 0.5 , 1 , 1.5 and 2 mg I ml media) . Two protocols were used to study the effect of garlic extracts on the mutagenicity of 8- MOP in the presence of UV A (366 nm) . In first protocol , the pretreatment method , all the concentrations (2.5 , 5 , 7.5 and 10 mg I ml ) of aqueous extract increased the mutants frequencies which were induced with 8-MOP + UV A, but only the low concentration (0.5 mg I ml) of the alcoholic extract increases the frequency of the mutants induced with 8- MOP + UV A . In the second protocol , the growth mediated method , both the aqueous and alcoholic extracts showed inhibitory effect on the mutagenicity of 8-MOP + UV A.